Security and Concurrency Control in Distributed Database System (International Journal of Scientific Research and Management (IJSRM), 2014)
This paper reviews the security issues and concurrency control in distributed database system. In this paper we have concerned about the features of distributed database system and its security issues. Distributed database is a collection of databases that can be stored at different computer network sites. This paper provides various aspects like fragmentation, types of fragmentation, replication and various problems that can be faced into distributed database system. The main goal of distributed database system design is to making fragmentation of the relations. Fragmentation is a design technique to divide two or more partitions such that the combination of the partitions provides the original database without any loss of data. By doing so, this reduces the amount of irrelevant data accessed by the applications of the database, thus reducing the disk accesses, which increases the performance of system.